2018
DOI: 10.1111/aos.13663
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary safety of ophthalmic beta‐blockers: a nationwide registry‐based cohort study

Abstract: Ophthalmic beta-blockers were associated with an increased risk of drug switch. However, the absolute risk was very small. No increased risk of new onset of obstructive pulmonary disease was found. Our data suggest that more patients might be eligible for ophthalmic beta-blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[28] A recent populationbased study of almost 100,000 patients newly prescribed IOP lowering treatment found that patients using medication for pulmonary disease had a significantly higher chance of stopping beta-blockers within 90 days of commencement compared to those without pulmonary disease (8% vs. 4%). [32] The rate of discontinuation of other IOP lowering medications was similar regardless of whether the patient had asthma or COPD.…”
Section: Pulmonary Safetymentioning
confidence: 86%
“…[28] A recent populationbased study of almost 100,000 patients newly prescribed IOP lowering treatment found that patients using medication for pulmonary disease had a significantly higher chance of stopping beta-blockers within 90 days of commencement compared to those without pulmonary disease (8% vs. 4%). [32] The rate of discontinuation of other IOP lowering medications was similar regardless of whether the patient had asthma or COPD.…”
Section: Pulmonary Safetymentioning
confidence: 86%